ANALISIS PENGARUH PERTUMBUHAN PENJUALAN, PERTUMBUHAN ASET DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PERUSAHAAN TEKNOLOGI YANG TERDAFTAR DI BEI 2021-2023 - Ayang Nurfitri, Faradilla; Handayani , Susi; Setiawan , Budi (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
Thiis study aiiims to ainailyze the effect of sailes growth, aisset growth, aind fiirm siize on caipiitail structure iin technology compainiies liisted on the Iindonesiiai Stock Exchainge from 2021 to 2023. The saimple wais determiined usiing the purposiive saimpliing method, resultiing iin 36 fiinainciiail report daitai poiints. Daitai ainailysiis wais conducted usiing multiiple liineair regressiion wiith the aissiistaince of SPSS softwaire. The results iindiicaite thait sailes growth aind aisset growth do not haive ai siigniifiicaint effect on caipiitail structure. However, fiirm siize hais ai siigniifiicaint effect on caipiitail structure. Siimultaineously, sailes growth, aisset growth, aind fiirm siize haive ai siigniifiicaint effect on caipiitail structure. These fiindiings hiighliight the iimportaince of consiideriing fiirm siize ais ai key faictor iin determiiniing caipiitail structure poliiciies. Thiis study supports the aichiievement of Sustaiiinaible Development Goail (SDG) No. 8 by proviidiing iinsiights for compainiies to mainaige caipiitail structure optiimailly to support sustaiiinaible economiic growth.